Knowledge and Acceptability of Cervical Cancer Screening among Adult Women Visiting in Gynecological OPD (Journal of College of Medical Sciences-Nepal, 2019)
Background: Cervical cancer is the most common form of cancer among women developing countries. Pap smear is a very significant screening test for reduction of incidence and mortality from cervical cancer. The pap smear test  detect precancerous cell change on the cervix that might become cervical cancer if they are not treated appropriately. The objective of this research is to find out the knowledge and acceptability of cervical cancer screening among adult women.Methods: A cross-sectional research design was conducted among 425 gynecological patients of Bharatpur hospital OPD of 30 to59 years of age. Semi structured questionnaire was used in data collection.Results: The mean age of participants was 40.07±7.9 years. Majority of the respondents, 247 (58.1%) had good knowledge in cervical cancer screening and 282 (66.4%) of the respondent accepted Pap smear test. Mean knowledge score on sign and symptom of cervical cancer was 62.1%, in risk factor was 72.8% and in preventive measure was 82%. Study showed the association between respondents knowledge of cervical cancer screening with educational status (p=0.04), religion (p=0.01) at 0.05 level of significance. There was association between respondents’ level of knowledge and acceptability of cervical   cancer screening (p=0.02) at 0.05 level of significance.Conclusions: Majority of participant had never screened for cervical cancer, information get from health care provider was poor and acceptability rate is low. So the study recommends that health care provider should provide the information education and communication (IEC) at all level of delivery towards cervical cancer screening.